2017
DOI: 10.1103/physreve.95.032146
|View full text |Cite
|
Sign up to set email alerts
|

Thermal rectification in mass-graded next-nearest-neighbor Fermi-Pasta-Ulam lattices

Abstract: We study the thermal rectification efficiency, i.e., quantification of asymmetric heat flow, of a one-dimensional mass-graded anharmonic oscillator Fermi-Pasta-Ulam lattice both with nearest-neighbor (NN) and next-nearest-neighbor (NNN) interactions. The system presents a maximum rectification efficiency for a very precise value of the parameter that controls the coupling strength of the NNN interactions, which also optimizes the rectification figure when its dependence on mass asymmetry and temperature differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 29 publications
(59 reference statements)
3
23
2
Order By: Relevance
“…This idea of increasing the energy flow by LR interactions was previously proposed and analytically investigated, but with an infinitesimal temperature gradient across the system [10]. In another recent work [11] it has been shown that the addition of next-nearest-neighbor interactions is already enough to increase the energy transport and thermal rectification in a mass-graded chain of anharmonic oscillators. In striking contrast, from the study of the LR-XY model it was concluded that the thermal conduction is "spoiled" in the presence of LR interactions [8].…”
Section: Introductionmentioning
confidence: 99%
“…This idea of increasing the energy flow by LR interactions was previously proposed and analytically investigated, but with an infinitesimal temperature gradient across the system [10]. In another recent work [11] it has been shown that the addition of next-nearest-neighbor interactions is already enough to increase the energy transport and thermal rectification in a mass-graded chain of anharmonic oscillators. In striking contrast, from the study of the LR-XY model it was concluded that the thermal conduction is "spoiled" in the presence of LR interactions [8].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we have proposed a thermal rectifier based on a 3D mass-graded FPU lattice formerly employed to verify the validity of Fourier's law in a system without an on-site potential [21]. Our first results seem to indicate that the behavior is very similar to that of the corresponding 1D lattice, especially in the fact that the obtained rectification is very small [25]. It is worth noting some interesting features of the shape of the temperature profiles depicted in Fig.…”
Section: Discussionmentioning
confidence: 76%
“…To overcome this limitation two ideas were proposed. The first one consists in using graded rather than segmented chains, i.e., chains where some physical property varies continuously along the site position such as the mass of particles in the lattice [20][21][22][23][24][25][26][27][28]. The second one uses particles with long range interactions (LRI), such that all the particles in the lattice interact with each other [21,29,30].…”
Section: Introductionmentioning
confidence: 99%